New nanocomposites of polystyrene with polyaniline doped with lauryl sulfuric acid - Pud, A. A. (Nanoscale Res Lett, 2017)
This work is concentrated on synthesis and investigation of new core-shell nanocomposites of polystyrene (PS) with doped polyaniline (PANI). The latex containing PS nanoparticles with sizes of 15–30 nm was prepared by microemulsion polymerization of styrene in water media. The PS/PANI nanocomposites were synthesized by chemical oxidative polymerization of aniline in the PS latex media in a presence of lauryl sulfuric acid (LSA), which served as both dopant and plasticizer. The real content of PANI in the synthesized nanocomposites was determined by UV-Vis spectroscopy method. The composition of the nanocomposites and oxidation state of the doped polyaniline were characterized by FTIR spectroscopy. The core-shell morphology of the nanocomposite nanoparticles was proved by transmission and scanning electron microscopy. It was found that conductivity and thermal behavior in air of these nanocomposites not only nonlinearly depended on the doped polyaniline content but also were strongly effected both by plasticizing properties of the acid-dopant and presence of the polyaniline shell. A possibility of application of these nanocomposites as sensor materials has been demonstrated.